Human Activity Recognition using wearable body sensor by machine learning approach - Promi, Sadia Tangim; Rahman, Md. Zahidur; Mostafa, Moumita; Harun, Sarah Bintay (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.